Competitive potential vs. the competitive position of the high-tech sector in European Union countries - Małgorzata Juchniewicz; Magdalena Łada (International Journal of Management and Economics, 2022)
Despite a considerable body of research and gathering information on advanced technologies, there is still a study gap concerning its importance from the perspective of international competitiveness. Therefore, a question arises: what affects the competitive potential and how does it contribute to the competitive position of the high-tech sector in European Union (EU) countries? For this reason, a study was taken up to evaluate the competitive potential and competitive position of the high-tech sector in EU countries. Defining the competitiveness, competitive potential, and competitive position in the industry was the starting point for the analysis. Further, selected indices were used to evaluate the competitive potential and to establish a competitive position. The synthetic competitiveness index was also calculated. The study identified the decisive factors having an impact on the competitive potential and competitive position of the sector and the relationship between them.
Keywords: O1; O3; 650; competitiveness; competitive position; competitive potential; European Union; high-tech sector